The Victory Stele of Dadusha of Eshnunna: A New Look at its Unusual Culminating Scene - Suter, Claudia E. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
The victory stele of Dadusha of Eshnunna is one of the few large-scale monuments to survive from Old Babylonian Mesopotamia. Although found in one piece, the surface on the front side carved in relief was partly damaged during recovery. According to its inscription, Dadusha dedicated the stele to the god Adad in celebration of his victorious military campaign against Qabara. A passage of this text, which can be identified as one of the earliest known ekphrases, describes the stele’s imagery. Some scholars consider the Dadusha Stele a rare example of a perfect match between text and image from ancient Mesopotamia. However, visual tradition does not confirm such a match. Several recent contributions, some of which appeared contemporaneously, propose divergent interpretations of the figures depicted in the culminating scene on the stele’s top register; the triumphant victor is precisely the figure most affected by the surface damages. This contribution provides a new perspective on the unusual culminating scene, suggesting that historical circumstance may have had a bearing on its final appearance.